Complementary Therapies in Cystic Fibrosis: Nutritional Supplements and Herbal Products. (February 2013) - Braga, Sarah F. Fowler; Almgren, Michaela M.
Cystic fibrosis is one of the most common autosomal recessive genetic disorders in caucasians of Northern European descent, affecting approximately 30 000 children and adults living in the United States, today. Complications of this chronic disease result in deterioration of lung function and development of pancreatic abnormalities requiring pharmacological therapy and may include patients seeking complementary and alternative option for treatment. Health care professionals should be knowledgeable of these therapies to effectively provide education and drug therapy management. This article offers an overview of the most common complementary therapies in cystic fibrosis such as vitamin A, vitamin C, vitamin E, zinc, omega 3 fatty acids, docosahexaenoic acid (DHA), garlic, ginseng, and curcumin.